Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.30955/gnj.002556
|View full text |Cite
|
Sign up to set email alerts
|

Universal Thermal Climate Index (UTCI) and synoptic circulation patterns over the metropolitan city of Athens, Greece

Abstract: <p>The present study aims to investigate the human thermal stress with respect to the synoptic scale circulation over the metropolitan city of Athens in Greece. The Universal Thermal Climate Index (UTCI) was applied in order to assess the levels of thermal stress employing three-hour meteorological data for four stations of the urban complex for a ten-year period (2006-2015). The patterns of the synoptic atmospheric circulation were classified in eight distinct categories based on a clustering scheme. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…This relative low frequency of the extreme categories could be due to the fact that UTCI was estimated using the ERA5-Land reanalysis dataset which although suitable and undoubtfully valuable, it may underestimate some weather variables compared to the surface meteorological stations (Araújo et al 2022;Zou et al 2022;Choudhury et al 2023) particularly in warm conditions (Choudhury et al 2023). Nevertheless, previous studies analyzing UTCI and using weather station data (Bleta et al 2014;Katavoutas and Flocas 2018;Pantavou et al 2023b), similarly reported either the absence or the extremely low frequency of the extreme UTCI categories, even though they considered regions in southern Greece (Bleta et al 2014) and Athens (Katavoutas and Flocas 2018;Pantavou et al 2023b). Different thermal indices may yield diverse estimations of thermal stress due to variations in their definitions and sensitivity to meteorological variables (Blazejczyk et al 2012;Provençal et al 2016;Pantavou et al 2023a).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This relative low frequency of the extreme categories could be due to the fact that UTCI was estimated using the ERA5-Land reanalysis dataset which although suitable and undoubtfully valuable, it may underestimate some weather variables compared to the surface meteorological stations (Araújo et al 2022;Zou et al 2022;Choudhury et al 2023) particularly in warm conditions (Choudhury et al 2023). Nevertheless, previous studies analyzing UTCI and using weather station data (Bleta et al 2014;Katavoutas and Flocas 2018;Pantavou et al 2023b), similarly reported either the absence or the extremely low frequency of the extreme UTCI categories, even though they considered regions in southern Greece (Bleta et al 2014) and Athens (Katavoutas and Flocas 2018;Pantavou et al 2023b). Different thermal indices may yield diverse estimations of thermal stress due to variations in their definitions and sensitivity to meteorological variables (Blazejczyk et al 2012;Provençal et al 2016;Pantavou et al 2023a).…”
Section: Discussionmentioning
confidence: 97%
“…The bioclimate of Greece is examined in studies of largescale investigations, such as global or Mediterranean-scale, using data at a relatively low spatial resolution (Di Napoli et al 2021a) or focusing on bioclimatic extremes (Giannaros et al 2018). The few studies specifically centered on Greece are concentrated to specific regions using data from the network of surface meteorological stations (Bleta et al 2014;Katavoutas and Flocas 2018). In previous nationwide studies (Matzarakis and Mayer 1997;Matzarakis et al 1999), data from a low number of surface stations and for one-hour daily values (at 12 UTC) were used, incorporating Predicted Mean Vote and PET for assessing the Greece bioclimate, while their findings require update.…”
Section: Introductionmentioning
confidence: 99%
“…The research also deals with the issue of the relationship between heat stress and atmospheric circulation. In this trend, Katavoutas and Flocas (2018) analysed metropolitan city of Athens in Greece, Rozbicka and Rozbicki (2018) in the south area of Warsaw and Gargol and Jakubowska (2014) in Cracow. Nowosad et al (2013) as well as Bartoszek et al (2017) conducted similar studies for Lesko and Lublin, while Bryś and Ojrzyńska (2016) for Wrocław.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of atmospheric circulation on bioclimatic conditions has been broadly investigated (Błażejczyk et al 2003, Bartzokas et al 2013, Nowosad et al 2013, Bryś, ojrzyńska 2016, Bartoszek et al 2017, katavoutas, Flocas 2018, Rozbicka, Rozbicki 2018, owczarek 2019, Głogowski et al 2020, Tomczyk, Owczarek 2020, Owczarek, Tomczyk 2022. Okoniewska (2021) evidenced that the most optimal biothermal conditions occur during the advection of marine polar air, extreme cold stress is caused by the inflow of polar continental and arctic air masses, and very strong heat stress by that of tropical air masses.…”
Section: Introductionmentioning
confidence: 99%